Exploring the dark side of third-party certification effect in B2B relationships: A professional financial services perspective - Cheng, Louis TW; Sharma, Piyush; Shen, Jianfu; Ng, Allen CC (Elsevier, 2021)
This paper extends the growing research on the dark side of B2B relationships by exploring the differences in third-party certification effects based on social capital with professional financial services firms, using a proprietary dataset with confidential voting records of the nominations for Investor Relation Awards in Hong Kong. Results confirm the dark side of these relationships by showing that the nominated firms with more favorable voting from international (vs. local) analysts experience stronger certification effect with higher valuations upon announcement. Moreover, nominated (but not awarded) firms with lower levels of information transparency demonstrate a larger certification effect but they also show significant improvement in their information transparency after the event, which represents an unexpected bright outcome from this dark side of B2B relationships. Overall, these findings extend the social capital argument that international financial services firms bring higher positive return through the support of their own professional and social network.